2012
DOI: 10.1093/carcin/bgs029
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin inhibits protein phosphatases 2A and 5, leading to activation of mitogen-activated protein kinases and death in tumor cells

Abstract: Curcumin can induce p53-independent apoptosis. However, the underlying mechanism remains to be defined. Here, we show that curcumin-induced apoptosis in a panel of tumor cells with mutant p53. Curcumin rapidly induced activation of the mitogen-activated protein kinases (MAPKs) including extracellular signal-regulated kinase 1/2 (Erk1/2) and c-Jun N-terminal kinase (JNK). Inhibition of JNK (with SP600125) or Erk1/2 (with U0126) partially prevented curcumin-induced cell death in the cells. Similarly, expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
58
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 49 publications
(98 reference statements)
3
58
1
Order By: Relevance
“…The mechanisms by which curcumin mediates its effects remain unclear. Several studies have demonstrated that curcumin acts as a free radical scavenger conferring cytoprotective effects; other research groups have remarked its prooxidant activity in tumor cells, favoring ROS generation and apoptosis (38,40). Further studies may contribute to elucidate the pro-oxidant and proapoptotic effects of curcumin at different doses in cancer cells and in the cochlea.…”
Section: E172mentioning
confidence: 99%
“…The mechanisms by which curcumin mediates its effects remain unclear. Several studies have demonstrated that curcumin acts as a free radical scavenger conferring cytoprotective effects; other research groups have remarked its prooxidant activity in tumor cells, favoring ROS generation and apoptosis (38,40). Further studies may contribute to elucidate the pro-oxidant and proapoptotic effects of curcumin at different doses in cancer cells and in the cochlea.…”
Section: E172mentioning
confidence: 99%
“…Accumulating data have shown that the phosphatase activity of PP2Ac is modulated by its association with PP2A-A, -B regulatory subunits [42]. Also the activity can be turned ''on'' and ''off'' by posttranslational modification such as phosphorylation and carboxyl methylation of PP2Ac [58,59]. Multiple studies have described that disturbances in the expression and/or function of PP2A are linked to autoimmune diseases [27,30,31].…”
Section: Discussionmentioning
confidence: 99%
“…At the same way, PP2A inhibitors have been reported as potential anti-cancer agents. 35 However, their potentiality in melanoma treatment has not been tested, yet.…”
Section: Discussionmentioning
confidence: 99%